Penampilan Lima Kultivar Jagung Madura - Achmad Amzeri (Agrovigor, 2009)
This research  aimed to evaluate important characters of a five of madura mays cultivars.  This research was conducted at Trunojoyo University Research Station, Bangkalan, Madura, on Juny to September 2008. Randomized block design with three replication used in this experiment, consisted of five treatment of genotypes (Tambin, Talango, Guluk-guluk, Manding and Kretek).  The observed characters were plant hight, male flowering date, female flowering date, cob hight, leaves number, leaves wide, leaves number on top of cob, long of cob, diameter of cob, diameter of jenggel, 1000-seed weight, production per hectare.  The result indicated that plant hight, female flowering date, leaves number, leaves number on top of cob, long of cob, diameter of cob, diameter of jenggel, 1000-seed weight, production per hectare in all five of the madura mays cultivars had significant difference.  The heritability estimates in the broad sense of production per hectare had medium heritability values in all five of madura mays cultivars.  There are possitive correlation between  production per hectare and  important characters in all five of madura mays cultivars.